2016
DOI: 10.1111/1346-8138.13286
|View full text |Cite
|
Sign up to set email alerts
|

The wound/burn guidelines – 5: Guidelines for the management of lower leg ulcers/varicose veins

Abstract: Varicose veins are treated at multiple clinical departments, but as patients often visit the dermatology clinic first due to leg ulcers, the present Guidelines for the Management of Lower Leg Ulcers/Varicose Veins were prepared in consideration of the importance of the dermatologist's role. Also, the disease concept of chronic venous insufficiency or chronic venous disorders and the CEAP classification of these disorders are presented. The objective of the present guidelines is to properly guide the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…The perforator veins of patients with a varix in the lower extremities are usually examined with ultrasonography or CE-CT (4). Ultrasonography is a useful modality because it is non-invasive and does not use ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perforator veins of patients with a varix in the lower extremities are usually examined with ultrasonography or CE-CT (4). Ultrasonography is a useful modality because it is non-invasive and does not use ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the guideline of the Society for Vascular Surgery and the American Venous Forum (1), “pathological” perforating veins are defined as those with an outward flow with a duration ≥500 ms, with a diameter ≥3.5 mm, and a location of beneath healed or open venous ulcers. The Japanese guideline for management of lower leg ulcers/varicose veins (4) defined the normal diameter of the communicating branches as ≥3 mm. Therefore, VR images that are reconstructed from 40-keV images are considered useful because pathologically dilated perforator veins can be depicted, but small perforator veins cannot be depicted.…”
Section: Discussionmentioning
confidence: 99%
“…Another algorithm was published later 23 in a study intended to validate the clinical efficacy and 23 Vowden and Vowden 24 Harding et al 25 Rutherford et al 12 Thomas 26 O'Donnell et al 27 Ratliff et al 28 Eklof et al 10 Vowden and Vowden 24 Widener 29 Harding 30 Krishnan and Nicholls 31 Eberhardt and Raffetto 14 Wittens et al 32 Franks et al 33 Vasquez et al 13 Harding et al 25 Ito et al 34 Lurie et al 11 Wittens et al 32 Tan et al 35 Hedayati et al 19 Ratliff et al 28 Alavi et al 36 Gould et al 37 the cost effectiveness of VLU guidelines in the United States and in the United Kingdom. This study demonstrated that implementation of a guideline for diagnosis and treatment of VLUs resulted in the improvement in diagnosis, decrease in healing time, and an increase in healing rates resulting in lower costs.…”
Section: Discussion Of Findings and Relevant Literaturementioning
confidence: 99%
“…En las guías de UV del European Dermatology Forum 62 , realizadas por el departamento de dermatología de Japón y en un trabajo realizado por la Universidad de California y de Harvard 63 , no se hace ninguna mención al uso de suplementos en pacientes con UV.…”
Section: úLceras Venosasunclassified